Corrigendum to “Engineering bispecific T-cell engagers to deplete eosinophils for the treatment of severe eosinophilic asthma” [Clinical Immunology 255 (2023) 109755] (Clinical Immunology (2023) 255, (S1521661623005181), (10.1016/j.clim.2023.109755)) - Kim, Jun Ho; Kim, Dae Seong; Park, Hae Sim; Kim, Yong Sung (Clinical Immunology, 2023)
The authors regret for not acknowledging funding from the Korea Health Industry Development Institute (KHIDI) in the original article. The grant number HI16C001 in the original article was incorrect. The correct grant number is HR16C0001. The complete acknowledgments section should read as follows: “This work was supported by the Korea Health Technology R&D Project grant ( HR16C0001) to YSK and HSP through the Korea Health Industry Development Institute (KHIDI), funded by the Ministry of Health & Welfare, and the Priority Research Center Program grant ( 2019R1A6A1A11051471) to YSK through the National Research Foundation of Korea (NRF), funded by the Ministry of Science, ICT, & Future Planning, Republic of Korea.” The authors would like to apologise for any inconvenience caused.